The Filipino woman and domestic violence determining the factors associated with women's risk of being a victim - Moleño, Dianne Therese D. (School of Economics, University of the Philippines Diliman, 2018)
This study explores the role of individual and household socioeconomic factors in predicting the incidence of intimate partner violence (IPV) in the Philippines. We analyze the determinants of IPV in light of prominent sociological theories _ (1) the Absolute Resource Theory (ART), (2) Household Bargaining Model (HBM), and (3) Male Backlash Model (MBM). We then determine which theory best predicts specific types of IPV _ whether physical, emotional or sexual IPV _ in the Philippine setting. Using data from the 2008 and 2013 National Demographic Health Survey, our logistics regression results reveal that ART and HBM best predict less severe physical violence while MBM best predicts sexual violence.